2018
DOI: 10.1155/2018/5238278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curing Conditions on the Shrinkage of Ultra High‐Performance Fiber‐Reinforced Concrete

Abstract: e effect of curing conditions on the early age and long-term shrinkage of ultra high-performance fiber-reinforced concrete (UHPFRC) was systematically studied. e shrinkage of the early age (0-168 h) and long-term age (0-90 d) of UHPFRC material was measured based on three kinds of humidity conditions (dry, sealed, and soaked) and curing temperatures (25°C, 40°C, and 75°C), respectively. In this paper, the hydration degree of different shrinkage stages was studied in combination with chemicalbound water experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Kostrzanowska-Siedlarz and Gołaszewski highlighted that the composition of the high performance SCC effect its rheological properties [ 1 ]. However, the methods of mixing and curing, together with the resistance of SCC to environmental conditions, are still under development [ 2 ]. Recently, the application of steel fibers has enabled the utilization of self-compacting high performance fibre-reinforced concrete (SCHPFRC).…”
Section: Introductionmentioning
confidence: 99%
“…Kostrzanowska-Siedlarz and Gołaszewski highlighted that the composition of the high performance SCC effect its rheological properties [ 1 ]. However, the methods of mixing and curing, together with the resistance of SCC to environmental conditions, are still under development [ 2 ]. Recently, the application of steel fibers has enabled the utilization of self-compacting high performance fibre-reinforced concrete (SCHPFRC).…”
Section: Introductionmentioning
confidence: 99%
“…These methods considered the addition of other cementations materials to hinder the early hydration and reduce the associated heat like fly ash and met kaolin, using crushed ice and lightweight aggregate for the purpose of internal curing, and increasing tensile strength by steel fibers. Kamen [13] and Hanet et al [16] stated that the high initial curing temperature raised the rate of autogenously shrinkage. Yang et al [14] showed the approaches that can be followed to mitigate the autogenously shrinkage depending on restraining agents inside the structure of UHPC.…”
Section: The Possible Ways To Reduce the Impact Of Autogenously Shrinkagementioning
confidence: 99%
“…Heat treatment anticipates significant amounts of the basic shrinkage, since the cement largely hydrates already during the treatment [ 18 ]. The specific influences on shrinkage depend on many factors such as the concrete’s composition [ 12 ] and can vary greatly [ 19 ].…”
Section: Introductionmentioning
confidence: 99%